Endoplasmic reticulum stress-mediated glycophagy drives macrophage M1 polarization in silica nanoparticles-induced pulmonary fibrosis - Lei Bao; Zihan Geng; Linpeng Niu; Lili Shi; Liyi He; Yaxian Pang; Cunhui Zhang; Yan Liu; Jiawei Chen; Beibei Shi; Ruiting Wu; Jingyuan Wang; et al. (Journal of Environmental Sciences, 2026)

Seed-associated Pseudomonas enhance the growth of Ambrosia trifida - Xue Chen; Chunying Li; Chang Wang; Jieyu Yang; Ruiting Ju; Fengjuan Zhang; Jihua Wu (Plant and Soil, 2026)

Chemical distance outweighs phylogeny in VOC-mediated cross-species plant defense communication - Chaonan Wang; Danfeng Liu; Xiao Xu; Mingjun Gao; Jiawei Wang; Jieren Jin; Yupeng Geng; Ruiting Ju; Yi Wang; Xiaoming Lu; Jihua Wu; Bo Li (Science China Life Sciences, 2026)

Climate-driven dynamics of surface water temperature and its coupled responses to lake heatwaves and cyanobacterial blooms in Lake Taihu - Lei Sun; Ruiting Xu; Yakun Feng; Haozhang Dai; Menglin Yuan; Chenhui Wu; Hao Wang; Ya Liu; Cuiling Jiang (Journal of Environmental Management, 2026)

Evolution and consistency analysis of plastic pollution control policies in East Asian Seas countries - Yang Deng; Danning Lu; Mahesh Pradhan; Panate Manomaiviboold; Kittiphon Boonma; Ruiting Wu; Toan Van Pham; Pattayaporn Unroj; Souvanna Phengsisombounf; Chuanbin Zhou (Marine Pollution Bulletin, 2026)

Repurposing hydrothermal carbonization aqueous product: Leveraging nitrification inhibition to drive a stable assimilatory metabolism for nutrient recovery - Ruiting Zhang; Hong Chen; Jun Sheng; Shiyi Zhao; Xin Yu; Dong Cheng; Hanyue Wu; Xiaoming Zou; Gang Xue (Chemical Engineering Journal, 2026)

Retraction notice to “Construction of functional curdlan hydrogels with bio-inspired polydopamine for synergistic periodontal antibacterial therapeutics” [Carbohydrate Polymers 245 (2020) 116585] - Xianqin Tong; Xiaoliang Qi; Ruiting Mao; Wenhao Pan; Mengying Zhang; Xuan Wu; Gang Chen; Jianliang Shen; Hui Deng; Rongdang Hu (Carbohydrate Polymers, 2026)

Multi-objective optimization of membrane-based dehumidification system for sustainable museum microclimates - Yilin Liu; Ruiting Wu; Junbao Fan; Lip Huat Saw; Liwen Jin (Building and Environment, 2026)

Invasion legacy weakens the positive effect of plant genotype diversity on soil multifunctionality - Wei Song; Cai Cheng; Zekang Liu; Shumeng He; Shenggui Xue; Xue Chen; Jingru Zhang; Lejie Wu; Qun Zhang; Guiyao Zhou; Yann Hautier; Ruiting Ju; et al. (Plant and Soil, 2025)

Carbon black induced pulmonary fibrosis through piR-713551/PIWIL4 targeting THBS2 signal pathway - Mengruo Wang; Yong Niu; Qingping Liu; Peihao Yang; Mengqi Wu; Ruiting Wu; Beibei Shi; Jiawei Chen; Jingyuan Wang; Zhe Du; Yaxian Pang; Lei Bao; et al. (Journal of Environmental Sciences, 2025)

Zinc Attenuates Cadmium and High-Fat Diet-Induced Cardiomyopathy by Enhancing Metallothionein-Mediated Cardiac Protection - Yaqin Liang; Yixiong Shi; Qiaoer Su; Chuangjie Gu; Ruiting Wu (Biological Trace Element Research, 2025)

Diffusion of sodium ions based on the interactions between gum arabic and oral mucin: Effects from the molecular weight of gum arabic - Yanlei Li; Ruiting Chang; Lin Lu; Zhiming Gao; Yuehan Wu; Wenxin Jiang; Dan Yuan; Katsuyoshi Nishinari (Food Chemistry, 2025)

Polystyrene bead ingestion promotes atherosclerosis plaque progression via BMP signaling in mice - Na Yang; Bo Wu; Xiaoxue He; Junhu Ma; Longhao Dai; RuiTing Ma; Tingting Yang; Xiaoxi Ning; Xiaoyan Li; Shaobin Jia (Food and Chemical Toxicology, 2025)

Freshness Prediction of Silver Carp Using Sub-Layer Equivalent Circuit Parameters in Electrochemical Impedance Spectroscopy - Jian Sun; Ruiting Xia; Feng Lin; Kai Wu; Jinfu Chen; Gangshan Wu; Wei Pan; Tingting Zou (Journal of Aquatic Food Product Technology, 2025)

The protective effect of two highly branched polysaccharides from corn silk fermented by Lactobacillus plantarum against acute liver injury - Yuxiang Wu; Ying Song; Ruiting Li; Ziyan Han; Liyin Li; Yishu Yan (Carbohydrate Polymers, 2025)

Sulfur cycle, a new opportunity for nitrogen removal from textile wastewater: A review - Shiyi Zhao; Hong Chen; Jun Sheng; Xin Yu; Kejia Zeng; Dong Cheng; Hanyue Wu; Ruiting Zhang; Xianbao Xu; Xiaoming Zou; Gang Xue (Journal of Water Process Engineering, 2024)

Layered deposited MoS2 nanosheets on acorn leaf like CdS as an efficient anti-photocorrosion photocatalyst for hydrogen production - Yao Wang; Tengyang Gao; Ruiting Li; Yan Chen; Wen Luo; Yang Wu; Yu Xie; Yong Wang; Yifan Zhang (Fuel, 2024)

Strengthening the diffusion of sodium ions by interactions between gum Arabic and oral mucin - Yanlei Li; Ruiting Chang; Duanyang Zhu; Lin Lu; Zhiming Gao; Yuehan Wu; Wenxin Jiang; Dan Yuan (Food Hydrocolloids, 2024)

Unraveling the generation mechanism of singlet oxygen in Bi2WxMo1-xO6 solid solution and roles in photocatalytic degradation of gaseous toluene under visible-light irradiation - Shaobo Cao; Lei Wu; Jun Li; Yang Li; Kang Da; Wenting Chen; Ruiting Xue; Jian Yang; Ximei Fan (Journal of Environmental Chemical Engineering, 2024)

Global meta-analysis and three-year field experiment shows that deep placement of fertilizer can enhance crop productivity and decrease gaseous nitrogen losses - Peng Wu; Qi Wu; Hua Huang; Lin Xie; Haoyuan An; Xintong Zhao; Fangtao Wang; Ziting Gao; Ruiting Zhang; Kemoh Bangura; Jianfu Xue; Min Sun; et al. (Field Crops Research, 2024)

Effects of Chaihu Shugan San on Brain Functional Network Connectivity in the Hippocampus of a Perimenopausal Depression Rat Model - Ruiting Huang; Min Gong; Xue Tan; Jianying Shen; You Wu; Xiaoshi Cai; Suying Wang; Li Min; Lin Gong; Wenna Liang (Molecular Neurobiology, 2024)

A photoelectrochemical aptasensor for omethoate determination based on a photocatalysis of CeO2@MnO2 heterojunction for glucose oxidation - Xingyang Wu; Jing Zhu; Ruiting Wen; Jiuying Tian; Jusheng Lu (Analytica Chimica Acta, 2024)

Genotype diversity enhances invasion resistance of native plants via soil biotic feedbacks - Cai Cheng; Zekang Liu; Qun Zhang; Xing Tian; Ruiting Ju; Bo Li; Mark van Kleunen; Jonathan M. Chase; Jihua Wu (Ecology Letters, 2024)
Although native species diversity is frequently reported to enhance invasion resistance, within‐species diversity of native plants can also moderate invasions. While the positive diversity–invasion resistance relationship is often attributed to competition, indirect effects mediated through plant–soil feedbacks can also influence the relationship. We manipulated the genotypic diversity of an endemic species, Scirpus mariqueter , and evaluated the effects of abiotic versus biotic feedbacks on the performance of a global invader, Spartina alterniflora . We found that invader performance on live soils decreased non‐additively with genotypic diversity of the native plant that trained the soils, but this reversed when soils were sterilized to eliminate feedbacks through soil biota. The influence of soil biota on the feedback was primarily associated with increased levels of microbial biomass and fungal diversity in soils trained by multiple‐genotype populations. Our findings highlight the importance of plant–soil feedbacks mediating the positive relationship between genotypic diversity and invasion resistance.

Permeability–Friction Relationships for Propped Fractures in Shale - Jiayi Yu; Jiehao Wang; Yan Li; Amr El-Fayoumi; Ruiting Wu; Xiaolong Liu; Peggy Rijken; Andrew P. Rathbun; Derek Elsworth (Rock Mechanics and Rock Engineering, 2023)

The role of total antioxidant capacity and malondialdehyde of seminal plasma in the association between air pollution and sperm quality - Lipeng Li; Tengfei Feng; Ruiting Wu; Yaling Zhang; Ning Wang; Mengqi Wu; Yaxian Pang; Sujuan Yang; Aimin Yang; Dengsuo Zhang; Guimin Hao; Rong Zhang (Environmental Pollution, 2023)

Linear charging-discharging of an ultralong UVA persistent phosphor for advanced optical data storage and wide-wavelength-range detector - Chuanlong Wang; Yahong Jin; Jiaxin Zhang; Xiangguang Li; Haoyi Wu; Ruiting Zhang; Qing Yao; Yihua Hu (Chemical Engineering Journal, 2023)

The impacts of urban anthropogenic heat and surface albedo change on boundary layer meteorology and air pollutants in the Beijing-Tianjin-Hebei region - Ruiting Liu; Zhiwei Han; Jiawei Li; Jie Li; Lin Liang; Yunfei Wu (Urban Climate, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Nebulization Therapy with Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes for COVID-19 Pneumonia - Meiping Chu; Hao Wang; Linjie Bian; Jiehui Huang; Danping Wu; Ruiting Zhang; Fangli Fei; Yigang Chen; Jiazeng Xia (Stem Cell Reviews and Reports, 2022)
Background Scientists have been facing numerous challenges in the development of an effective therapeutic strategy for the treatment of COVID-19 pneumonia. Several studies have suggested that improving patient immunity and reducing lung injury induced by SARS-CoV-2 may be effective for treating patients with COVID-19. Methods A pilot trial of nebulization therapy with exosomes of mesenchymal stem cells (MSCs) was performed on seven patients with COVID-19 pneumonia. Exosomes secreted from MSCs were collected and purified using multiple ultrafiltration steps. All patients were treated with nebulization of MSC-derived exosomes, and primary safety and efficacy outcomes were evaluated. Results Our clinical study demonstrated that nebulization of MSC-derived exosomes is a novel method that might be utilized in the treatment of COVID-19 pneumonia. Nebulization of MSC-derived exosomes did not induce acute allergic or secondary allergic reactions but did promote the absorption of pulmonary lesions and reduce the duration of hospitalization for mild cases of COVID-19 pneumonia. Conclusions Nebulization of MSC-derived exosomes is a safe, effective, and simple method, and their application at the beginning of treatment may be more beneficial. Trial Registration Chinese Clinical Trial Registry, ChiCTR2000030261. Registered on 26 February 2020. Graphical Abstract

White Matter Free Water is a Composite Marker of Cerebral Small Vessel Degeneration - Peiyu Huang; Ruiting Zhang; Yeerfan Jiaerken; Shuyue Wang; Hui Hong; Wenke Yu; Chunfeng Lian; Kaicheng Li; Qingze Zeng; Xiao Luo; Xinfeng Yu; Xiao Wu; et al. (Translational Stroke Research, 2022)

Semi-synthetic product dihydroartemisinin inhibited fibronectin-1 and integrin-β1 and interfered with the migration of HCCLM6 cells via PI3K-AKT pathway - Ruiting Wu; Yan Gao; Jiaqin Wu; Chunli Wang; Li Yang (Biotechnology Letters, 2020)

Responses of soil biota and nitrogen availability to an invasive plant under aboveground herbivory - Jiahui Zhou; Ruiting Ju; Bo Li; Jihua Wu (Plant and Soil, 2017)

Numerical Modeling of Hydraulic Fractures Interaction in Complex Naturally Fractured Formations - Olga Kresse; Xiaowei Weng; Hongren Gu; Ruiting Wu (Rock Mechanics and Rock Engineering, 2013)